2021
DOI: 10.1080/20502877.2021.1917101
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic Healthcare Resource Allocation, Age and Frailty

Abstract: The current coronavirus pandemic presents the greatest healthcare crisis in living memory. Hospitals across the world have faced unprecedented pressure. In the face of this tidal wave of demand for limited healthcare resources, how are clinicians to identify patients most likely to benefit? Should age or frailty be discriminators? This paper seeks to analyse the current evidence-base, seeking a nuanced approach to pandemic decisionmaking, such as admission to critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Previous studies reported similar findings when health care professionals felt unable to care for all patients equally due to resource issues and had to choose between the well-being of one patient over another. In line with other studies, the triage criteria for prioritizing patient care based on age or health state during the pandemic caused ethical conflicts and dilemmas for participants (Booke & Booke, 2021;Palacios-Ceña et al, 2022;Smithard & Haslam, 2021).…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies reported similar findings when health care professionals felt unable to care for all patients equally due to resource issues and had to choose between the well-being of one patient over another. In line with other studies, the triage criteria for prioritizing patient care based on age or health state during the pandemic caused ethical conflicts and dilemmas for participants (Booke & Booke, 2021;Palacios-Ceña et al, 2022;Smithard & Haslam, 2021).…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, previous studies 29,30 have described a great variability in the criteria for prioritizing patient care during the COVID-19 pandemic, which can lead to conflicts and ethical dilemmas among healthcare professionals. 31,32 For example, showing differences in triage between older and younger patients. 31 Due to the existence of differences in models and approaches regarding prehospital and hospital triage, we believe there is an important need for ethical frameworks to clarify the values and principles that will guide caregivers while addressing the unique societal needs.…”
Section: Communitymentioning
confidence: 99%
“…31,32 For example, showing differences in triage between older and younger patients. 31 Due to the existence of differences in models and approaches regarding prehospital and hospital triage, we believe there is an important need for ethical frameworks to clarify the values and principles that will guide caregivers while addressing the unique societal needs.…”
Section: Communitymentioning
confidence: 99%
“…The Coronavirus disease 2019 (COVID-19) pandemic resulted in the reconfiguration of health service provision in England and worldwide [ 1 , 2 ]. Health services were re-purposed, clinicians redeployed, and non-emergency treatments delayed.…”
Section: Introductionmentioning
confidence: 99%